Imaging Diagnosis of Adenomyosis - O'Shea, Aileen; Figueiredo, Gabrielle; Lee, Susanna I. (Seminars in Reproductive Medicine, 2020)
Uterine adenomyosis can be diagnosed on ultrasonography (US) and magnetic resonance imaging (MRI) with a high degree of accuracy. Adenomyosis is a myometrial process that can appear as diffuse or focal on imaging. Diffuse adenomyosis typically causes uterine enlargement, while focal adenomyosis can mimic other myometrial lesions, such as leiomyomas. Imaging features frequently seen on US include a heterogenous thickened myometrium and myometrial cysts. On MRI, widening of the junctional zone, whether focal or diffuse, and the presence of myometrial cysts, either simple or hemorrhagic, support the diagnosis of adenomyosis. Despite these characteristic imaging appearances, there are several gynecologic pathologies which can mimic adenomyosis and it is important to be vigilant of these when interpreting cross-sectional imaging exams. The decision to evaluate patients with US or MRI is contingent on multiple factors, including availability of the necessary technology and expertise for the latter. However, MRI appears to offer greater specificity and positive predictive value for the diagnosis of adenomyosis.
Keywords: magnetic resonance imaging; ultrasonography; adenomyosis